2021
DOI: 10.1080/10641955.2021.1965621
|View full text |Cite
|
Sign up to set email alerts
|

Coronavirus disease 2019 (COVID-19) and the risk of hypertensive disorders of pregnancy: a retrospective cohort study

Abstract: Purpose: To evaluate the association of hypertensive disorders of pregnancy with SARs-CoV-2 infection in pregnant women.Methods: We conducted a retrospective cohort study of all pregnant patients with positive SARs-CoV-2 molecular test at four participating hospitals located in a large metropolitan city and who delivered between February 1 st and November 24 th , 2020. Patients who tested positive during their pregnancy and delivered (index cases) were compared to the three subsequent deliveries of patients wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 40 publications
1
7
0
Order By: Relevance
“…In sections of our study on the association between COVID‐19 and maternal hypertension states, including preeclampsia, we found that the probability of maternal hypertension was increased in pregnant women with COVID‐19. In some studies, including meta‐analyses, a relationship was found between COVID‐19 and maternal hypertensive diseases in parallel with our study 12–15 . The possible reasons for the relationship between COVID‐19 and maternal hypertension are not clearly known.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…In sections of our study on the association between COVID‐19 and maternal hypertension states, including preeclampsia, we found that the probability of maternal hypertension was increased in pregnant women with COVID‐19. In some studies, including meta‐analyses, a relationship was found between COVID‐19 and maternal hypertensive diseases in parallel with our study 12–15 . The possible reasons for the relationship between COVID‐19 and maternal hypertension are not clearly known.…”
Section: Discussionsupporting
confidence: 75%
“…In some studies, including meta-analyses, a relationship was found between COVID-19 and maternal hypertensive diseases in parallel with our study. [12][13][14][15] The possible reasons for the relationship between COVID-19 and maternal hypertension are not clearly known. The source of this relationship may be due to the possibility that SARS-CoV-2 may bind to angiotensin-converting enzyme 2 receptors, leading to renin-angiotensin system dysfunction and vasoconstriction.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of both diseases likely had either a synergistic or an opportunistic effect, which may have led to severe clinical manifestations via the interplay of the renin-angiotensinogen-aldosterone system in their pathogenesis." Baracy et al 18 "When comparing only COVID-19 positive pregnancies, early infection conferred a significantly higher risk for HDP than late infection. This observation is consistent with the inflammatory explanation of increased HDP risk in COVID-19.…”
Section: Authormentioning
confidence: 99%
“…Testing positive for SARS-CoV-2 during pregnancy has been shown to increase the risk of developing a hypertensive disorder of pregnancy (OR: 3.68). 73 This has significant potential impacts to both the mother and her child, as hypertensive disorders of pregnancy can lead to an increased risk of preterm birth, intrauterine growth restriction, miscarriage, stillbirth, and maternal complications including stroke and maternal death. 74 Long-term risks for the infant include neurodevelopmental delay and complications of prematurity.…”
Section: Pregnancy-related Cerebrovascular Events and Covid-19mentioning
confidence: 99%